PENGARUH KUALITAS PELAYANAN, KUALITAS PRODUK, DAN STORE ATMOSPHERE TERHADAP KEPUASAN PELANGGAN PADA COFFFEE SHOP MAMBAL - Kadek Anggi Trisnayanti; I Gusti Ayu Imbayani; I Made Surya Prayoga (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2023)
Every company is required to provide satisfaction to consumers so that business people can maintain their business on an ongoing basis with other companies. Great attention to customer satisfaction is most important because satisfied customers will tend to be loyal to the company. This study aims to determine the effect of service quality, product quality, and store atmosphere on customer satisfaction at Coffee Shop Mambal. In this problem, the population to be used is consumers at Coffee Shop Mambal whose number is unknown. The sampling technique was carried out using a purposive sampling method, so the number of samples in this study were 120 consumers at the Mambal Coffee Shop. The data analysis technique used to answer the hypothesis is multiple linear regression analysis. The results of this study indicate that brand image has a positive and significant effect on customer loyalty in service quality. Service quality has a positive and significant effect on customer satisfaction at Coffee Shop Mambal. Product quality has a positive and significant effect on customer satisfaction at Coffee Shop Mambal. Store atmosphere has a positive and significant effect on customer satisfaction at Coffee Shop Mambal.